BAGURAU SALUANG DAN DENDANG DALAM PERSPEKTIF PERUBAHAN BUDAYA MINANGKABAU (Faculty of Social Science, Universitas Negeri Semarang, 2008)
Minangkabaunes art performance which is played by women, both traditional and modern(contemporary) art performance, is a change in Minangkabaunes culture life. We know that Minangkabaunessociety uses matrilineal system. It means that women have special position, especially in keepingâ€œMinangkabaunes culture moralâ€. Women were like â€œthe center of Minangkabaunes cultureâ€ as revealedin a proverb â€œpusek jalo pumpunan ikanâ€. In Minangkabaunes culture tradition, women are limited toexpress their selves in public art performance. Moreover, in professional art performance, it seems to beforbidden. Women only performed often in culture activity which was part of Minangkabaunes traditionalceremony. But the world changes, and so does Minangkabaunes society. In these four last decades, manyMinangkabaunes women have performed in Minangkabaunes art performance like bagurau saluangand dendang show. It is an interesting phenomenon in Minangkabaunes culture. The development ofMinangkabaunes women in show art reflects the change and movement in Minangkabaunes culture whenit is related to Minangkabaunes matrilineal culture tradition. There were many rules in Minangkabaunesculture which forbid women to perform in art performance activities. But now, that forbidden rule hasbeen a part of reality in Minangkabaunes culture itself.Keywords: Women, art, change